Penile ulcer as a specific clinical manifestation of Waldenstrom's macroglobulinemia - Cláudia Cardoso de Macedo Oliveira; José Antônio Nascimento Bressa; Fernanda Mendes; Eduardo Vinicius Mendes Roncada; Rodrigo Monteiro; Marilda Aparecida Milanez Morgado Abreu (Sociedade Brasileira de Dermatologia, 2016)
Abstract Waldenstrom's macroglobulinemia is considered a lymphoma by the World Health Organization. Cutaneous lesions, particularly of a specific type, are rare occurring in 5% of patients. What draws attention in this case is the unusual cutaneous clinical manifestation and its location on the genitals, which has not been described in researched literature, therefore imposing differential diagnosis with other etiologies of genital ulcers.